A new leaf pubescence gene, Hl1th, introgressed into bread wheat from Thinopyrum ponticum and its phenotypic manifestation under homoeologous chromosomal substitutions - A. V. Simonov; E. I. Gordeeva; M. A. Genaev; W. Li; I. O. Bulatov; T. A. Pshenichnikova (Вавиловский журнал генетики и селекции)
Blue-grain lines were created on the basis of the spring bread wheat variety Saratovskaya 29 (S29) with chromosome 4B or 4D replaced with chromosome 4Th from Thinopyrum ponticum. The leaf pubescence of the two lines differs from S29 and from each other. In this work, we studied the effect of these substitutions on the manifestation of this trait. To quantify pubescence, the LHDetect2 program was used to determine trichome length and number on the leaf fold microphotographs. The key gene Hl1 on chromosome 4B and another unidentified gene with a weak effect determine the leaf pubescence of the recipient S29. Their interaction leads to the formation of trichomes of up to 300 microns in length. Replacement of both copies of chromosome 4B with two copies of wheatgrass chromosome 4Th modifies leaf pubescence in line S29_4Th(4B) so that the leaf pubescence characteristic of S29 becomes more sparse, and trichomes of up to 600–700  µm in length are formed. Additionally, we described modification of pubescence in the substitution line S29_4Th(4D) where chromosome 4D that does not carry any pubescence gene was replaced. Under this substitution, trichomes of up to 400 µm in length were formed and the average length of trichomes on the underside of the leaf was reduced. The replacement of the Hl1 gene in the lines was also confirmed by the allelic state of the linked microsatellite marker Xgwm538. Thus, as a result of the studies, a new leaf pubescence gene introgressed from Th. ponticum into bread wheat was identified. We designated it as Hl1th. For the purpose of selection, we propose to use the unlicensed informative microsatellite markers Xgwm538 and Xgwm165, allowing chromosomes 4A, 4B, 4D and 4Th to be distinguished.